Cost Savings and Reduced Health Care Utilization Associated with Participation in a Digital Diabetes Prevention Program in an Adult Workforce Population - Cynthia Castro Sweet; Carolyn Bradner Jasik; Amy Diebold; Ashley DuPuis; Bryan Jendretzke (Journal of Health Economics and Outcomes Research)
**Background:** Though in-person delivery of the Diabetes Prevention Program (DPP) has demonstrated medical cost savings, the economic impact of digital programs is not as well understood.